Optimal design of prestressed concrete hollow core slabs taking into account its fire resistance. (August 2018) - Albero, V.; Saura, H.; Hospitaler, A.; Montalvà, J.M.; Romero, Manuel L.
Highlights: A design procedure for the hollow core slab cross-section optimization is presented. The hollow core optimal design includes the fire resistance and taking into account all available manufacturing technologies. The hollow core optimal design obtained saves up to 20% in cross-section area. Precast designers should use optimization techniques to modify their designs. Abstract: Prestressed hollow core slabs are a concrete element widely used as construction floor product, which manufacturing process has greatly been improved in recent years. Several research studies focused on hollow core slab performance, mainly related to its fire behavior, have provided new limit states to be assessed throughout its life cycle. Therefore, the hollow core slab design needs to be reviewed to allow for these improvements, a process which may involve changes to its geometry. In order to deal with this review, modern computational optimization techniques offer an alternative approach to traditional structural product design procedure, mainly based on the engineer's prior experience. This paper proposes a hollow core slab model (including variables and constraints) to develop heuristic search algorithms, such as simulated annealing, in order to find the most economical slab design including the fire resistant constraint and taking into account all available manufacturing technologies. The optimal designs obtained by this process save up to 20% in cross-section area compared with common circular void designs from market, which is taken as a comparison pattern. The results show that traditional designs are deficient when the fire resistant constraint is considered, so that precast manufacturers and machinery designers should use optimization techniques to modify their hollow core slab geometry.